👤
a fost răspuns

-6√5 + √3 {[ 2√3 · (√8 + √5 ) + 6√15 ] : 4 + √6 } =                   R: 6√2
| 3√3 - 5 | + 7 - 6√3 =                                                            R:2-3√3
| 5√2 - 7 | - 8√8 =                                                                  R: -7-11√2

  Multumesc anticipat!


Răspuns :

-6√5 + √3 {[ 2√3 · (√8 + √5 ) + 6√15 ] : 4 + √6 } =
=-6√5 + √3 {[ 2√3 · (2√2 + √5 ) + 6√15 ] : 4 + √6 } =
=-6√5 + √3 [( 4√6 + 2√15  + 6√15 ) : 4 + √6 ] =
=-6√5 + √3 [( 4√6 + 8√15 ) : 4 + √6 ] =
=-6√5 + √3 (2√6 + 2√15 )  =
=-6√5 + 2√18 + 2√45  =
=-6√5 + 6√2 + 6√5  = 6√2


| 3√3 - 5 | + 7 - 6√3 =
= 3√3 - 5 + 7 - 6√3 = 2-3√3

| 5√2 - 7 | - 8√8 =
 5√2 - 7  - 16√2 =  -7-11√2